Vincent Buckley: The City and the Sacred (Journal of the Association for the Study of Australian Literature, 2013)
A reading of Buckley's 'The Golden Builders' that argues it embodies the idea, proposed by the postmodern atheologian Mark C. Taylor, that deconstruction is a particular realisation of incarnation.